Demand and Supply Analysis of Transport Energy in Pakistan - Shah, Syed Ale Raza; Anwar, Sofia; Naqvi, Syed Asif Ali (International Journal of Contemporary Economics and Administrative Sciences, 2019)
Over the last decade, the importance of energy consumption in transport sector has burgeoned forth and has been growing rapidly in Pakistan, and the course is being augured to linger over the coming decades. This paper brings about the function of transport energy demand, economic growth (GDP), oil rents, gas rents, road length and number of registered vehicles for Pakistan over the 1980-2015 by using Autoregressive Distributive Lag (ARDL) approach. The results which have had come about shows preponderance of the fact that there is powerful relationship between all concerned variables when transport energy demand is used as a dependent variable in Pakistan. Hence, Autoregressive Integrated Moving Average (ARIMA) model is used for the future forecasting related to the consumption and production of gasoline and oil. According to the forecasted results, consumption (demand) is much greater as compared to production (supply) in both non-renewable sources. As policy makers suggest, we can make up for this lacuna by bourgeoning forth new technology (hybrid vehicles) as well as an awareness campaign through which we can make others abreast of this research may be launched about energy conservation methods to curtail the transport energy demand (TED) in the country.